PERJUANGAN PEREMPUAN DALAM ARENA POLITIK (STUDI PEMILIHAN ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH DI KABUPATEN MIMIKA, PROPINSI PAPUA DALAM PRESPEKTIF PIERRE BOURDIUE) - Sopia Wadanubun; Antik Tri Susanti; Elly E. Kudubun (UNIVERSITAS SEBELAS MARET (UNS), 2020)
Women are constructed as second-class creatures. This prejudice then gets reinforced in the moral structure of society manifested in religious and customary regulations. However, in the political arena an effirmative policy has been set up by giving a 30% quota of permaan. This study wants to find out how women struggle in the political arena, using the perspective of Pierre Bourdieu. The approach used in this study is a qualitative research approach, which is a research procedure that produces descriptive data using interview, observation, and document utilization techniques. This study concludes that gender is not a matter of unsuccessful person in the election stage. This means that men and women have the same opportunity to be chosen. Election is determined by the amount of economic capital. Because economic capital is the dominant determinant of victory, not because of the issue of women's struggle, in practice it can be predicted that the struggle against women's rights will not have a place in the political arena in Mimika Regency, Papua Province.Keywords: Women, Politics, Arena, Pierre Bourdieu, Capital AbstrakPerempuan dikonstruksikan sebagai makhluk kelas dua, prasangka ini kemudian mendapatkan penguatan dalam struktur moral masyarakat yang terwujud dalam peraturan-peraturan agama maupun adat, namun demikian dalam arena politik telah di tetapkan kebijakan affirmative dengan memberi perempuan tkuota 30%.Penelitian ini ingin mengetahui bagaimana perjuangan perempuan dalam arena politik, dengan menggunakan perspektif Pierre Bourdiue, pendekatan yang di lakukan dalam penilitian ini adalah jenis pendekatan penelitian kualitatis yaitu suatu prosedur penelitian yang menghasilkan data deskriptif menggunakan teknik wawancara, pengamatan dan pemanfaatan dokumen.Penelitian ini menyimpulkan bahwa gender bukan merupakan persoalan ketidak berhasilan seseorang dalam tahap pemilihan, artinya laki-laki dan perempuan mempunyai peluang yang sama untuk di pilih. Tentununya keterpilihan seseorang di tentukan oleh jumlah modal ekonomi.Kata kunci : Perempuan,Politik, Pierre Bourdiue, Modal